2021
DOI: 10.12911/22998993/133964
|View full text |Cite
|
Sign up to set email alerts
|

Biological, Physico-Chemical and Morphological Analyses of Four Biochars Derived from Agricultural Waste

Abstract: Around the world, the increasing population and consumption are placing huge demands on food. Agriculture is considered one of the important sectors in the world and the force to feed humanity. While under these circumstances, which stand out by successive years of drought, degradation of soil, climate change, and global warming, this sector has multifaceted a major issue that goes beyond threatening food security. Thus, Morocco characterized by an arid and semi-arid climate is one example of countries that su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…When compared to carbonate, oxalate may be less successful at neutralizing acidic soils [19]. The calcite formed, as a result, contributed to the alkalinity of the banana-waste biochar investigated, as seen by their high pH values of 9.30 [9]. In addition, the FTIR technique's results can be utilized as an effective tool for controlling biochar quality in production circumstances, and, as a result, its impacts on plant growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When compared to carbonate, oxalate may be less successful at neutralizing acidic soils [19]. The calcite formed, as a result, contributed to the alkalinity of the banana-waste biochar investigated, as seen by their high pH values of 9.30 [9]. In addition, the FTIR technique's results can be utilized as an effective tool for controlling biochar quality in production circumstances, and, as a result, its impacts on plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…This result was surprising for us; in fact, the increase in the two-fluorescence activity can be explained by amending with banana-waste biochar and compost mixtures. When banana-waste biochar was studied with a scanning electron microscope in a prior study, it revealed a number of pores [9]. Indeed, the porosity of the studied biochar helped soils to maintain more water and nutrients even in harsh conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The waste feedstock of banana leaves was pyrolyzed in a Moroccan pyrolysis process heater based on a model by Prof. Claudia Kammann (Bouqbis et al 2016). The detailed physicochemical properties of banana waste biochar have previously been reported (Fetjah et al 2021a). In turn, compost was purchased from Agadir.…”
Section: Experimental Designmentioning
confidence: 99%
“…The banana waste biochar was produced at 201 °C according to the method elaborated by Bouqbis and Fetjah [Bouqbis et al, 2016;Fetjah et al, 2021].…”
Section: Experiments Designmentioning
confidence: 99%